Anatomy of the bacterium - Malatay Monar, Carlos (Revista Universidad de Guayaquil, 1994)
Living beings are made up of morphological elements that make up architecture or anatomy and fluids that give biological dynamism: these two elements together establish functions that are the expression of the life of the being. In the second half of the sixteenth century, Antonie Van Leecuwenhoch discovered microorganisms in the microscopes he made (1) and two centuries later Louis Pasteur determined their functions, beneficial functions that help in the production of wine and beer.
Keywords: Capsule; Outer membrane